Diagnostic potential of lysosomal hydrolases in body cavity effusions. Issue 2 (February 1976) - McCormack, M
Abstract : Hexosaminidase, alpha-mannosidase, beta-galactosidase, beta-glucuronidase, and arylsulphatase A were measured inperitoneal and pleural effusions from patients with benign, malignant, and inflammatory disorders. Compared with the benign transudates, all enzyme activities were moderately elevated in malignant effusions and markedly elevated in inflammatory effusions. The assay of hexosaminidase and and alpha-mannosidase indicated clearly the underlying pathology in most specimens studied. This method could be of clinical value when the cause of an effusion is in doubt, particularly since the diagnostic criteria are independent of the presence or absence of tumour cells in the aspirate.